Решить уравнение: (х-7)(х+7)-(х+10)(х-1)=4х

Svetbor04 Svetbor04    3   10.05.2020 17:11    0

Ответы
zarina20178 zarina20178  14.09.2020 08:27

x = - 3

Объяснение:

(х - 7)(х + 7) - (х + 10)(х - 1) = 4х

x² - 49 - (х + 10)(х - 1) = 4х

x² - 49 - (x² - x + 10x - 10) = 4х

x² - 49 - (x²  + 9x - 10) = 4х

x² - 49 - x²  - 9x + 10 = 4х

- 49 - 9x + 10 = 4x

-39 - 9x = 4x

-9x - 4x = 39

- 13x = 39

x = 39 : (- 13)

x = - 3

ПОКАЗАТЬ ОТВЕТЫ
tanyakozina00 tanyakozina00  14.09.2020 08:27
Решение на фото! Надеюсь Вам
Решить уравнение: (х-7)(х+7)-(х+10)(х-1)=4х
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра